Study of quality of life and its correlated factors in patients after lumbar fusion for lumbar degenerative disc disease - Chen, Meng; Peng, Da-Yong; Hou, Wen-Xiu; Li, Yang; Li, Jing-Kun; Zhang, Hao-Xuan (Frontiers in Surgery, 2023)
Background In the present work, we aimed to explore the correlated factors of quality of life in patients receiving lumbar fusion for lumbar degenerative disc disease (DDD) in China. Methods A total of 180 patients treated with lumbar fusion were included in the present study. Their general demographic characteristics, Visual Analog Scale (VAS) scores, Japanese Orthopedic Association (JOA) scores, Simplified Coping Style Questionnaire (SCSQ), Social Support Questionnaire (SSQ), and Medical Outcomes Study Short Form 36 (MOS SF-36) were collected and evaluated preoperatively and at 1 year postoperatively. Results There were significant improvements in scores of VAS, JOA, and quality of life of patients from preoperation to 1-year postoperation after lumbar fusion. Marital status, with or without children, education level, economic pressure, and social support had significant predictive effects on the physical health of patients undergoing lumbar fusion. Marital status, education level, and economic pressure had significant predictive effects on the mental health of patients undergoing lumbar fusion. Conclusions Factors correlated with the physical health of patients after lumbar fusion included positive coping style, negative coping style, social support, age, education level (high school college), disease duration (5~10), suffering from other diseases (combined with two or more other disease) and the number of surgical segments (double and three or more). Factors correlated with the mental health included negative coping style, social support, age, education level (middle school and high school college) and the number of surgical segments (double and three or more). The results verify that these factors were correlated to the patient's quality of life after lumbar fusion. Emphasizing and selectively intervening these correlated factors can further improve the quality of life in patients receiving lumbar fusion for lumbar degenerative disc disease.